The George Washington Bridge : poetry in steel - Rockland, Michael Aaron (Rutgers University Press, 2020)
Presents perspectives on the George Washington Bridge spanning history, architecture, engineering, transportation, design, the arts, politics, and even post-9/11 mentalities. This new edition brings new insight since its initial publication in 2008, including a new chapter on the infamous "Bridgegate" Chris Christie-era scandal of 2013.--